2021
DOI: 10.26508/lsa.202000948
|View full text |Cite
|
Sign up to set email alerts
|

Urinary prostaglandin E2 as a biomarker for recurrent UTI in postmenopausal women

Abstract: Urinary tract infection (UTI) is one of the most common adult bacterial infections and exhibits high recurrence rates, especially in postmenopausal women. Studies in mouse models suggest that cyclooxygenase-2 (COX-2)–mediated inflammation sensitizes the bladder to recurrent UTI (rUTI). However, COX-2–mediated inflammation has not been robustly studied in human rUTI. We used human cohorts to assess urothelial COX-2 production and evaluate its product, PGE2, as a biomarker for rUTI in postmenopausal women. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…Based on these findings, Ebrahimzadeh and colleagues ( 72 ) assessed urinary prostaglandin E2 (PGE2), which is a product of arachidonic acid conversion by the COX-2 enzyme, as a biomarker for rUTI in a cohort of 92 postmenopausal women (31 women with acute UTI and a rUTI history, 35 women with rUTI but without an active infection and 26 healthy controls). They found a positive association between urinary PGE2 concentration and urothelial COX-2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, Ebrahimzadeh and colleagues ( 72 ) assessed urinary prostaglandin E2 (PGE2), which is a product of arachidonic acid conversion by the COX-2 enzyme, as a biomarker for rUTI in a cohort of 92 postmenopausal women (31 women with acute UTI and a rUTI history, 35 women with rUTI but without an active infection and 26 healthy controls). They found a positive association between urinary PGE2 concentration and urothelial COX-2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The physiologically relevant PGE2 level in human urine ranges from 500 to 5000 pg/mL. 23 Figure S9 shows the characteristic response curves for both EIS and MS methods. Calibrated sensor dose responses for PGE2 detection in synthetic urine (pH 6) are depicted in Figure S5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…From literature, it has been found that urine PGE2 levels elevated above 2000 pg/mL are indicative of active rUTI in postmenopausal women and concentrations below this level are consistent with women who do not have active UTI or rUTI. 23 This threshold was utilized for spike and recovery analysis to evaluate the efficacy of dose-response experiments and the sensor's ability to distinguish between "no-UTI" and "active-UTI" cases (Figure 5). Thus, the signal response at PGE2 dose concentration of 2000 pg/mL was used as the threshold dose as the UTI classification threshold for classifying test urine sample as UTI positive or negative.…”
Section: T H Imentioning
confidence: 99%
See 2 more Smart Citations